Perceptions and attitudes on the management of HIV and AIDS : in the Department of Agriculture, Conservation, Environment and Tourism of North West province in Republic of South Africa / Pheletso Abednigo Mothibedi - Mothibedi, Pheletso Abednigo (2014)
The researcher is propelled and motivated by the Minister of Public Service Association, Geraldine Frasser-Moleketi, recognising the serious nature of HIV and AIDS and its impact on South Africa when she initiated the Impact and Action Project in January 2000, which was aimed at ensuring that Public Service is able to sustain a quality service in spite of pandemic: AIDS. The apprehension of writing on the theme is to enlighten both the employer and employees with their obligations, rights and legal framework in the management of the pandemic: AIDS within the employment perspective. The eminence of the study is based on the participation of management and their intervention, because without their involvement, AIDS deaths translate into lost productivity, increased high rate of absenteeism, short or long illnesses, and lower morale of employees and hampering of rendering of services. The study comprises of five chapters, containing the orientation of the study; literature review; research design and methodology; data analysis and results and summary, findings and recommendation, respectively. The instrument employed to gather data was applied in five regions, and data is gathered from a target sample of 96 out of 2084 employees. Please note in order to avoid the continuous use of "HN and AIDS", virus, epidemic, disease or cumbersome descriptions, the noun pandemic: AIDS, will be used and will denote "HIV and AIDS". === MBA (HRM) North-West University, Mafikeng Campus, 2005